Exercise-based cardiac rehabilitation and atherosclerotic plaque regression in ASCVD: Is exercise really a game-changer? A scoping review of controlled trials - Dwita Rian Desandri; Averina Octaxena Aslani; Faqrizal Ria Qhabibi; Dimitra Nikoletou (PLoS ONE, 2026)
Exercise-based cardiac rehabilitation (CR) has emerged as a promising strategy for promoting atherosclerotic plaque regression in patients with atherosclerotic cardiovascular disease (ASCVD). Although lipid-lowering drugs are firmly established for plaque regression, the impact of exercise-based CR on plaque regression remains underexplored, prompting synthesis of existing evidence. This review aims to characterize studies on exercise-based CR in ASCVD, summarize CR modalities, identify confounding factors, and evaluate evidence of plaque regression from imaging and clinical outcomes. A thorough literature search was conducted in May-June 2025 across PubMed, ScienceDirect, and EBSCO. Included studies were controlled trials on CR for ASCVD adults assessing plaque changes via imaging. Data extraction followed PRISMA-ScR guidelines focusing on study design, populations, interventions, and outcomes. Five trials encompassing 217 participants demonstrated that diverse CR programmes—high-intensity interval training, aerobic exercise and resistance training—combined with standard medical therapy significantly reduced plaque volume parameters, as measured by IVUS and carotid ultrasound. CR further improved key mechanistic markers, including inflammatory cytokines and endothelial function, underpinning plaque stabilization and regression. Exercise-based CR robustly promotes plaque regression and mitigates cardiovascular risk in ASCVD, complementing pharmacological approaches. These findings affirm CR’s indispensable role in secondary prevention, though confounding from concurrent lipid-lowering therapies warrants consideration in future randomized trials.